Women Rights Violation and the Role of Islam in Bangladesh - Mizi, Mohammed Anowar Hossain (MAQOLAT: Journal of Islamic Studies, 2025)
Women rights violation is a common phenomenon in the world be it developed, developing and under developed country. If we closely observe the life of our prophet and Islamic culture we will find that there is no place of violence against women in Islam. Although Bangladesh is predominantly a Muslim country there are wide spread violence and abuse of women human rights in Bangladesh. None of the violence and women rights abuse are sanctioned by Islam. Non-Islamic culture has been infiltrated into Islam and this culture provokes women’s rights violation. Strict adherence to prophetic teachings and observance of Islamic culture can stop women rights violation and uphold women rights in Bangladesh.